Yoga Philosophy in the Shrimad Bhagavad Gita: A Study : श्रीमदभागवत गीता में योगदर्शन एक अध्ययन - Yadav, Jayant Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Yoga philosophy is an important discipline that is highly beneficial for spiritual seekers. The Yoga philosophy, authored by Maharishi Patanjali, is divided into four sections: Samadhi Pada, Sadhana Pada, Vibhuti Pada, and Kaivalya Pada. It considers the restraint of mental modifications (Chitta Vritti Nirodha) as the foundation of yoga. Samadhi Pada describes Nirbija Samadhi as the ultimate goal, while Sadhana Pada explains the eightfold path (Ashtanga Yoga). Vibhuti Pada discusses yogic powers, and Kaivalya Pada emphasizes mental purification and liberation. Yoga philosophy paves the way for the realization of the true self. Abstract in Hindi Language: योग दर्शन एक महत्त्वपूर्ण शास्त्र है, जो साधकों के लिए अत्यंत उपयोगी है। महर्षि पतंजलि कृत योग दर्शन चार भागों में विभाजित है: समाधि पाद, साधन पाद, विभूति पाद, और कैवल्य पाद। इसमें चित्तवृत्ति निरोध को योग का मूल आधार माना गया है। समाधि पाद में निर्विज समाधि को अंतिम लक्ष्य बताया गया है। साधन पाद में अष्टांग योग की व्याख्या की गई है। विभूति पाद में योग की सिद्धियों का वर्णन है, जबकि कैवल्य पाद में चित्त की शुद्धि और मोक्ष की अवस्था पर बल दिया गया है। योग दर्शन आत्मा की स्वरूप प्रतिष्ठा का मार्ग प्रशस्त करता है। Keywords: समाधि पाद, साधन पाद, विभूति पाद